Polymer Processing and Surfaces - Sedlačík, Michal (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on fundamental and applied research on polymer processing and its effect on the final surface as the optimization of polymer surface properties results in the unique applicability of these over other materials. The development and testing of the next generation of polymeric and composite materials is of particular interest. Special attention is given to polymer surface modification, external stimuli-responsive surfaces, coatings, adhesion, polymer and composites fatigue analysis, evaluation of the surface quality and microhardness, processing parameter optimization, characterization techniques, among others.